Synthesis of fumed silica supported amino-Pd complexes and their catalytic performance for Heck reaction - Hu, Guo-Hui; Zhou, Jian-Min; Yang, Yu-Lin; Li, Xiao-Kun; Zhou, Ren-Xian; Zheng, Xiao-Ming (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2009)
Using fumed silica as supporter, chain amino and cyclic amino as functional reagents, a series of fumed silica supported amino-palladium(II) complexes were prepared by coordination reaction followed by reduction. The catalysts were characterized by IR, XRD, XPS, ICP. The effect of the preparation condition and difference of ligand on the catalytic performance was studied. Its catalytic performance for Heck reaction of iodobenzene with acrylic acid showed that the catalyst has high activity at 70~90. The product takesEform. The catalyst after reduction had high catalytic activity and good recycling performance. With the increase of number of N atoms, there was a rising trend of catalytic activity for those catalysts which contain chain amino ligand. And the catalytic activity was much lower for those catalysts which contain cyclic amino ligand.